Activities of various quinolone antibiotics against Mycobacterium leprae in infected mice. - Gelber, R H (1992)
Previously, pefloxacin and ofloxacin were found to be active against Mycobacterium leprae in vitro, in experimental animals, and in clinical trials of lepromatous leprosy patients. In this study, we compared certain more recently developed fluoroquinolones (lomefloxacin, PD 124816, WIN 57273, temafloxacin, and sparfloxacin) with pefloxacin and ofloxacin in M. leprae-infected mice at doses of 50, 150, and 300 mg/kg given five times weekly. All seven of the fluoroquinolones studies were active against M. leprae; temafloxacin and sparfloxacin were the most active, being fully bactericidal at all three dosage schedules. Additionally, sparfloxacin was found to be fully bactericidal at 15 and 30 mg/kg given five times weekly.